The citizen of two worlds: The new identity of Psychoanalysis - Di Maria, Alessio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2018)
The post-modern man is a Narcissus is seeking his identity. The Evaporation of the Father has changed the dynamics of relationship with the Other and the ability to build one’s own identity has to resort to consumer objects. This study proposes a path that goes from the classical theory of Psychoanalysis to a new perspective that enters the field of Marketing and the study of the object of consumption.